A thermal resistant and flame retardant separator reinforced by attapulgite for lithium-ion batteries via multilayer coextrusion. (22nd June 2022) - Li, Yajie; Yang, Haicun; Ahmadi, Azita; Omari, Aziz; Pu, Hongting
Abstract: Multilayer separators are widely used due to their wide shutdown window by combining lower melting temperature and higher melting temperature of different layers. With the development of high power lithium-ion batteries, multilayer separators equipped with effective thermal stability and flame retardancy are highly required. Herein, the poly(methyl methacrylate) modified attapulgite (ATPM) is selected as the heat resistant reinforcing component and blended with polypropylene (PP)/polyethylene (PE) respectively. Then we prepare PP(ATPM)/PE(ATPM) separators via multilayer coextrusion efficiently without multiple stretching processes, which can avoid serious separator shrinkage at elevated temperature. The intertwined ATPM could not only enhance the separator integrity, but also produce water vapor and oxide anti-flaming isolation layers at high temperatures. The as-prepared separators, referred to as MC-TIPS PP/PE/ATPM, exhibit higher thermal stability (with negligible dimensional shrinkage up to 180 °C), better flame retardancy and wider shutdown temperature window (124–183 °C) than the commercial multilayer separators. Moreover, the introduction of ester and hydroxyl groups could improve the wettability and electrolyte uptake of the separators. These properties, as well as the potential for large-scale production of multilayer coextrusion, make MC-TIPS PP/PE/ATPM an ideal choice for high-power battery separators. Graphical abstract: Image 1 Highlights: A robust multilayer separator of polypropylene and polyethylene reinforced by poly(methyl methacrylate) modified attapulgite (ATPM) is prepared via multilayer coextrusion without multiple stretching processes, then can avoid serious separator shrinkage at elevated temperature. The addition of hydrous and heat-resistant ATPM can not only enhance thermal integrity of separator, but also produce water vapor/oxide anti-flaming isolation layers at high temperature, thus improve the flame retardancy of separator. This preparation method can be extended to fabricate other multilayer separators by choosing other suitable polymeric matrix and reinforce filler (inorganic nanowire/fibre, flame retardant powder, etc).